Carnarvon based SARAO staff and students perceptions of the NRF|SARAO’s Human Capacity Development in the Northern Cape, South Africa - Andreas, Naslynne D.P; Binneman, Anton; Nguepi Kasse, Sophie (Journal of Economic Development, Environment and People, 2022)
The Karoo Region in the Northern Cape Province, South Africa was identified as a site to establish a large section of the Square Kilometer Array (SKA) which will feature the world’s largest Radio telescope, a project being spearheaded by the NRF|SARAO through the construction of The MeerKAT Radio telescope that will be integrated in the SKA. Owing to the documented shortage of skilled workforce particularly in the field linked to the SKA project, the NRF|SARAO has a role to play in developing skills in the Northern Region in line with the Skills Development Act No. 97 of 1998 to promote productivity and national development. This study explores the human capacity development (HCD) programs offered by the NRF|SARAO and surveyed 17 participants to document their perceptions towards the HCD programs. Respondents acknowledged the HCD programs being offered by the NRF|SARAO to train them and become involved in the SKA project. Various hindrances that affects the success of the HCD programs were raised which have to do with both the respondents themselves and their perceptions, as well as the standards that are set by the NRF|SARAO which at times hinder the potential candidates to take up the programs. Respondents’ had varied views towards the effectiveness of the NRF|SARAO programs which varied between highly effective to not effective at all.